Moral hazard in health care: case study of Taiwan's national health insurance - Lin, Chun-Wei, author; Fan, Chuen-Mei, advisor; Mushinski, David, committee member; Pena, Anita Alves, committee member; Loomis, John B., committee member (Colorado State University. Libraries, 2012)
My research examines the moral hazard phenomenon under Taiwan's National Health Insurance system theoretically as well as empirically. The objective is to investigate the effects of universal health insurance on individual lifestyle behavior such as smoking and alcohol consumption. In the analytical section, I incorporate the individual's copayment rate, the premium, and the payroll tax rate in a moral-hazard model of national health care insurance plan. The two-stage for individual decision is applied to an extension of the moral hazard model originally proposed by Ehrlich and Becker (1972) and Stanciole (2007). In stage one, an individual moves first and decides his / her optimal unhealthy behavior before knowing the health status. In stage two, once the health status is revealed, he/she will move to choose the optimal amount of medical care after stage one. By applying the backward induction method, I show that after individuals falling sick in stage two, the optimal demand for medical service decreases when faced with a higher payroll tax rate, a higher copayment rate, a higher premium, and a higher medical service price. However, an individual's optimal demand for medical service increases with the individual's income level, poor health status and with the addiction of unhealthy behavior. In stage one, the individual's optimal unhealthy behaviors decrease with a higher copayment rate, a higher payroll tax rate, a higher premium, a higher medical price and with poor health status; but increase with income level. The effect from medical service is ambiguous. I also examine how three government policy parameters -copayment rate, premium, and payroll tax rate - affect individual's welfare given his/her lifestyle under the universal health insurance system. My model results suggest that the copayment rate has an ambiguous effect on individual's well-being. Payroll tax rate and Premium have positive effects on the individual's well-being. In my empirical investigation, I use two waves of the Health and Living Status of the Middle- Age and Elderly (SHLS) survey in Taiwan (1993 and 2007). Lifestyle behaviors (smoking and alcohol consumption) are employed as dependent variables. In my econometric model, I use a univariate Probit model and a seemingly unrelated bivariate Probit model to measure the determinants of unhealthy lifestyle behavior in 1993 and 2007. Two lifestyle behaviors - smoking and alcohol consumption - are employed as dependent variables in my model. Lastly, I apply a difference-in-difference (DD) methodology to compare how these effects change before and after implementation of Taiwan's national health insurance system. The result shows a lack of evidence in my data for the effect of national health insurance, implying no moral hazard effect is found under Taiwan's National Health Insurance.
Keywords: lifestyle behavior; national health insurance; moral hazard